Pengembangan Potensi Wisata Alam Curug Panganten di Desa Tanjungsari Kecamatan Sadananya Kabupaten Ciamis - Ade Elsa Nuranisa; Arie Budiawan; Ersa Mitha Alutgusti; Eman Sulaeman (Universitas 17 Agustus 1945, 2025)
The development of tourist villages is one of the strategic efforts to maximize local potential while improving community welfare. Tourist villages not only focus on the exploration of natural and cultural resources but also involve local communities as the main subjects in management. Tanjungsari Village, Sadananya District, Ciamis Regency, has natural tourism potential that can be developed into a tourist village, one of which is Curug Panganten which is a water tourism. However, it has not run optimally, several problems have hampered its development, such as the lack of competent tourist village managers and the absence of village regulations (Perdes) as a legal basis for tourism management. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and literature studies. The data obtained were analyzed to understand the characteristics and obstacles faced in the development of tourist villages. The results of the study show that the potential for Curug Panganten tourism in Tanjungsari Village has not been managed optimally due to the lack of human resources trained in tourism management and the absence of regulations that systematically regulate tourism management and development. In addition, community involvement and support from the local government still need to be improved to create a sustainable tourist village. The hope for the future is that the formation of Perdes can be the first step in realizing a more structured tourism management, followed by training for tourism managers to increase capacity and professionalism. With clear regulations and good management, Tanjungsari Village is expected to develop into a competitive tourist destination and provide economic and social benefits for the local community.